ETIMON PROTO AUSTRONESIA (PAN) PADA BAHASA ALORES DI PULAU ALOR NUSA TENGARA TIMUR - Ida Ayu Iran Adhiti (Widyadari : Jurnal Pendidikan, 2019)
Analysing Austronesia Purba language based on tradisional analysis becomes the attention of comparative linguistics, such as reconstruction and grouping as genetically the hereditary languages in south east islands. Austronesia language has the most vast area in the world, from Madagaskar to Easter island. Then it developed in Indonesia, Malaysia, Philippins and Madagascar. The observation on local languages in Indonesian needs to be done especially local language that developes in Alor island. Alores language is classified Austronesian language that is analysed from eighteen language exist in Alor island. Besides, Alores language is the biggest local language in Alor island from the classification of spreading area and the distance of speaker area. The trace of Alores language is done through the approach of comparative historic linguistics from the list of 200 Swadesh vocabularies. The etimon determination uses the trace in dictionary of Proto Austronesia (PAN) that is constructed by Wurm and Wilson. Then, the etimon category is grouped in Alores language. The number of nomina etimon is 71, verba etimon is 70, verba adjectiva is 36, verba adverbial is 20, and pronominal is 3. The number of etimon that throw out from Proto Austronesian (PAN) is 43. It is showed that Alores language is hereditary from Proto Austronesian (PAN) that is developed and maintained in Alor island until now.